PHARMACOLOGICAL MANAGEMENT PREECLAMPSIA IN PREGNANT WOMEN : LITERATURE REVIEW - Annisya Awalia; Sukmawati Sukmawati; Witdiawati Witdiawati (Journal of Maternity Care and Reproductive Health, 2020)
Preeclampsia is major cause of maternal and fetal mortality and morbidity. The incidence of preeclampsia in Indonesia has increased every year. One of the efforts to prevent complications from preeclampsia requires pharmacological management. The purpose of this study was to determine pharmacological management of pregnant women with preeclampsia. The design of this study was literature review with narrative review type. The strategy used to search Indonesian literature used the keyword penatalaksanaan OR menejemen klinis  AND farmakologi AND preeklampsia, for foreign language Intervention OR management clinic AND pharmacology AND preeclampsia. The data base used was Google Scholar and Pubmed. The inclusion criteria in this study were full text articles in Indonesian and English, samples of pregnant women with preeclampsia, published years of articles in 2010-2020, articles on pharmacological management of preeclampsia, articles on pharmacological treatment of preeclampsia, articles obtained in the literature search for this review as many as 604 articles that were analyzed according to the focus of the research were 10 articles. The result of the review found 3 interventions, namely procedures/SOP for the treatment of preeclampsia, types of drugs for preeclampsia, and the cost effectiveness of antihypertensive drugs. The conclusion was that there were 3 interventions in the pharmacological management of preeclampsia in pregnant women, namely procedures/SOP for preeclampsia, types of drugs for preeclampsia, cost effectiveness of antihypertensive drugs. The result of this literature review is expected to be information material for health workers in treating patients with various types of antihypertensive drugs, dosages and methods of action for preeclampsia cases.